Signal Transduction Mechanisms Quantitatively Observed One Molecule at a Time - Li, Pei; Chen, Ting; Chen, Liang; Tan, Yan-Wen (Frontiers in Physics, 2022)
Improved single-molecule methods can largely increase our understanding of underlying molecular mechanism during cellular signal transduction. In contrast to conventional bulk methods, monitoring molecules one at a time can circumvent averaging effects and acquire unique information. With single-molecule techniques, quantitative characterizations can be achieved at microscopic level, especially for biochemical systems with strong heterogeneity. Here we review four fundamental single-molecule techniques including total internal reflection fluorescence imaging, single-molecule fluorescence recovery after photobleaching, single-molecule Förster resonance energy transfer, and fluorescence correlation/cross-correlation spectroscopy. These techniques are frequently employed in quantitatively investigating the molecular translocation, protein-protein interactions, aggregations, and conformational dynamics involved in the signal transduction both in vitro and in vivo. We also summarized the basic principles and implementations of these single-molecule techniques, as well as the conjunct applications extending the single-molecule measurements to multiple dimensions.